Effect of play therapy in reduction of postoperative pain perception among the children aged 6-12 years in All India Institute of Medical Sciences, Patna - Saima; S., Ramya; Jain, Hansmukh; Sinha, Amit Kumar (International Journal of Contemporary Pediatrics, 2025)
Background: Postoperative pain in children remains a significant concern, often leading to delayed recovery and distress. This study evaluated the effect of play therapy on postoperative pain among children aged 6-12 years in AIIMS Patna. Methods: A quasi-experimental, non-randomized control group design was used. The 54 children meeting inclusion criteria were selected through non-probability convenience sampling from pediatric surgery wards. Demographic data were collected from parents and children. Pain was assessed on postoperative days 1-4 using the Wong-Baker FACES pain rating scale (WBPS). The experimental group received 50 minutes/day of play therapy; the control group received standard care without intervention. Data were analyzed using descriptive and inferential statistics. Results: In the experimental group, 16 (59.3%) children reported ‘pain whole lot.’ 6 (22.2%) ‘pain even more.’ and 5 (18.5%) ‘pain little more.’ In the control group, 14 (51.9%) experienced ‘pain even more’ and 13 (48.1%) ‘pain whole lot.’ Post-test mean pain scores were 1.37±0.742 (experimental) and 3.37±0.792 (control) at p=0.001, confirming significant reduction in pain with play therapy. Experimental group pre-test mean was 3.41±0.797, with a mean difference of 2.04 post-therapy (p=0.001). Control group change was not significant (p=0.537). Significant associations were found between age (p<0.013) and postoperative sedation (p<0.012) with post-test scores in the experimental group; no associations were observed in the control group. Conclusions: Play therapy is effective in reducing postoperative pain perception in children aged 6-12 years.